Factors Affecting Implementation and Perceived Changes in the New Social Studies Curriculum: Erbil, Sulaymaniyah and Duhok Regions in Iraq as an Example - Qolamani, Khalid Ilias Basheer; Kaya, Erol; Ünlü, İhsan; Kaşkaya, Alper (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2025)
This study investigates the factors affecting implementation and perceived changes in the New Social Studies Curriculum across Erbil, Sulaymaniyah, and Duhok regions in Iraq. Through semi-structured interviews with twenty social studies teachers, the research identifies and analyzes key implementation factors including resource availability, time constraints, teacher training, student engagement, assessment methods, administrative support, and curriculum alignment. The findings reveal significant implementation challenges related to curriculum complexity, teacher preparedness, and regional variations in resource distribution. Teachers reported evolving professional roles, from content delivery to facilitating critical thinking, fostering historical empathy, and promoting cultural appreciation. The study contributes to curriculum implementation theory by demonstrating how contextual factors in post-conflict settings influence reform efforts, while providing evidence-based recommendations for enhancing professional development, resource provision, and administrative support to improve implementation effectiveness across the three regions.